2015
DOI: 10.1371/journal.pmed.1001796
|View full text |Cite
|
Sign up to set email alerts
|

CD47 Agonist Peptides Induce Programmed Cell Death in Refractory Chronic Lymphocytic Leukemia B Cells via PLCγ1 Activation: Evidence from Mice and Humans

Abstract: BackgroundChronic lymphocytic leukemia (CLL), the most common adulthood leukemia, is characterized by the accumulation of abnormal CD5+ B lymphocytes, which results in a progressive failure of the immune system. Despite intense research efforts, drug resistance remains a major cause of treatment failure in CLL, particularly in patients with dysfunctional TP53. The objective of our work was to identify potential approaches that might overcome CLL drug refractoriness by examining the pro-apoptotic potential of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
93
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(100 citation statements)
references
References 81 publications
7
93
0
Order By: Relevance
“…Together with the novel anti-CD20 obinutuzumab [152] and other promising agents (the BCL2 inhibitor ABT-199 [153], the XPO1 inhibitor selinexor [154], CD47 agonist [155]), these treatments may exert different pressure on CLL clonal evolution and may modify prognostic stratification and evolutionary trajectories, as evaluated until now.…”
Section: Discussionmentioning
confidence: 99%
“…Together with the novel anti-CD20 obinutuzumab [152] and other promising agents (the BCL2 inhibitor ABT-199 [153], the XPO1 inhibitor selinexor [154], CD47 agonist [155]), these treatments may exert different pressure on CLL clonal evolution and may modify prognostic stratification and evolutionary trajectories, as evaluated until now.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, when considering targeting of CD47 or SIRPα it should be mentioned that at least some agents have been shown to exert direct effects on cancer cell growth. For instance, triggering CD47 on the cell membrane of several hematological cancers resulted in a direct inhibition of cancer cell growth or lead to the induction of caspase‐dependent or ‐independent apoptotic cell death in vitro(see Table ). Finally, we showed that an antibody directed against SIRPα triggered caspase‐independent apoptosis in SIRPα‐expressing acute myeloid leukemic cells, and this antibody also synergized with various chemotherapeutics for triggering cell death …”
Section: Cd47‐sirpα Interactions As An Immune Checkpoint In Cancermentioning
confidence: 99%
“…More recently, CD47 activation by peptides derived from the C‐terminal domain of TSP‐1 induces a caspase‐independent and calcium‐dependent cell death in different cancer cell lines . Indeed, CD47 engagement to PKHB1, the first‐described serum‐stable soluble CD47‐agonist peptide, induced changes in ER morphology, CRT exposure, reactive oxygen species (ROS) production and dissipation of the mitochondrial membrane potential in cells from patients with CLL …”
Section: Introductionmentioning
confidence: 99%